Staplerová linie u sleeve resekce žaludku - Zonča, P; Guňková, P; Martínek, L; Foltys, A; Bužga, M; Jacobi, C A (Rozhledy v chirurgii, 2013)
INTRODUCTION: Postoperative leak and bleeding from the staple line are potentially serious early complications following laparoscopic sleeve gastrectomy. AIM: This study aims to assess the significance of oversewing the staple line after laparoscopic sleeve gastrectomy in preventing leak and bleeding in our group of patients. MATERIAL AND METHODS: Patients after laparoscopic sleeve gastrectomy were included in the trial. Two different principles of oversewing the staple line (selective vs. mandatory) were analyzed. The design of the trial was retrospective-prospective, non-randomized. Postoperative complications were recorded. RESULTS: Between October 2006 and December 2011, 638 laparoscopic sleeve gastrectomies were carried out using standard laparoscopic technique. 297 of the patients belonged to the group with selective oversewing of the staple line. The remaining 341 patients belonged to the group in which the staple line was oversewn in all cases. Both groups of patients were comparable in the basic parameters. Early postoperative leak affected one patient in both groups, 0.30% versus 0.29% (p = 0.9203), respectively. The rates of postoperative bleeding were 2.7% (selective oversewing) versus 0% (mandatory oversewing) (p = 0.0023), respectively. CONCLUSION: Our study did not demonstrate the impact of oversewing the staple line on the occurrence of postoperative leak. The rates of postoperative bleeding from the resection site were statistically significantly lower in the group with the mandatory oversewing of the staple line.
Keywords: Surgical Stapling; gastrektomie; Humans; laparoskopie; lidé středního věku; Gastrectomy; Female; dospělí; lidé; Adult; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Retrospective Studies; chirurgická technika pomocí přístrojů a svorek; Laparoscopy; retrospektivní studie; mužské pohlaví; prospektivní studie; Prospective Studies